2017
DOI: 10.1002/jez.b.22754
|View full text |Cite
|
Sign up to set email alerts
|

Review: Biological and Molecular Differences between Tail Regeneration and Limb Scarring in Lizard: An Inspiring Model Addressing Limb Regeneration in Amniotes

Abstract: Tissue regeneration in lizards represents a unique model of regeneration and scarring in amniotes. The tail and limb contain putative stem cells but also dedifferentiating cells contribute to regeneration. Following tail amputation, inflammation is low and cell proliferation high, leading to regeneration while the intense inflammation in the limb leads to low proliferation and scarring. FGFs stimulate tail and limb regeneration and are present in the wound epidermis and blastema while they disappear in the lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
97
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 49 publications
(101 citation statements)
references
References 75 publications
3
97
0
1
Order By: Relevance
“…Embryos have an absent to weak adaptive immune system, their tissues develop and mature before the adaptive immune system, and a perfect wound healing or regeneration can only occur in embryonic‐like stages (Adzick & Longaker, ; Deuchar, ; Nodder & Martin, ). The production of high levels of hyaluronate and high tissue hydration together the activation of embryonic signaling pathways, innervation and vascularization, stimulate regeneration or tumor growth (Alibardi, , ; Boilly, Faulkner, Jobling, & Hondemarck, ; Csoka & Stern, ; Nambiar et al, ; Ross & Gordon, ; Kiricuta & Simplaceanu, ). Regenerating limbs and tails of adult amphibians show that they possess a soft consistency similar to those of the embryos (Figure a–e).…”
Section: Regeneration In Vertebrates Requires the Formation Of Blastemasmentioning
confidence: 99%
“…Embryos have an absent to weak adaptive immune system, their tissues develop and mature before the adaptive immune system, and a perfect wound healing or regeneration can only occur in embryonic‐like stages (Adzick & Longaker, ; Deuchar, ; Nodder & Martin, ). The production of high levels of hyaluronate and high tissue hydration together the activation of embryonic signaling pathways, innervation and vascularization, stimulate regeneration or tumor growth (Alibardi, , ; Boilly, Faulkner, Jobling, & Hondemarck, ; Csoka & Stern, ; Nambiar et al, ; Ross & Gordon, ; Kiricuta & Simplaceanu, ). Regenerating limbs and tails of adult amphibians show that they possess a soft consistency similar to those of the embryos (Figure a–e).…”
Section: Regeneration In Vertebrates Requires the Formation Of Blastemasmentioning
confidence: 99%
“…I, therefore, hypothesize that as long as high levels of hyaluronate remains localized around mesenchymal and epidermal cells of the blastema, the circulating lymphocytes and macrophages cannot assess their cell surface and no immune reaction is elicited. Previous studies indicated that the levels of hyaluronate decrease from the apical blastema in the proximal regions as in the latter cells differentiate into new tissues so that only the apical, mesenchymal blastema remains temporary unaffected from the immune system until regeneration is completed (Alibardi, ; Alibardi & Sala, ).…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, it is clear that the blastema in regenerative‐competent vertebrates has numerous characteristics of neoplasm outgrowths, including the high production of hyaluronate (Alibardi, ; Csoka & Stern, ). Different from tumors, the blastema has the capacity to regulate its multiplication and growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The new tail appears to be an uncompleted copy of the original one and its functionality, in terms of bending and curling, is very limited, except in some geckos (Alibardi & Meyer‐Rochow, ). Past and present evidence have indicated that two tissues of epithelial type are essential for maintaining proliferation of the mesoderm tissues: The apical wound epidermis and the ependymal tube derived from the original spinal cord (Alibardi et al, ; Alibardi, ; Alibardi, ; Lozito & Tuan, ; Simpson, ).…”
Section: Introductionmentioning
confidence: 99%